PARASIT DALAM LUKISAN REALIS KONTEMPORER - SYUKRA MAYUDHA, Drs. Erfahmi,M.Sn., Drs. Efrizal, M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose of the creation of this final work is to remind the community hw deviant behavior is increasingly happening around the environment, not only in the community but also in the community. The method of creating this final work uses 5 stages, namely the preparation stage, elaboration stage, synthesis stage, concept realization phase, and completion stage, and the exhibition. The works using acrylic paint media on canvas with contemporary realist patterns. Ten of the works that were visualizing parasites as metaphors, by tittle (1) Jalur, (2) Ketidakpuasan, (3) Hinggap, (4) Rumah, (5) Melilit, (6) Hidup, (7) Muncul, (8) Taenia, (9) Kedaluarsa, (10) Busuk, in contemporary realist painting.Kata kunci: Parasit, metafor, seni lukis.